Universality of fragmentation in the Schr\"odinger dynamics of bosonic Josephson junctions - Sakmann, Kaspar; Streltsov, Alexej Iwanowitsch; Alon, Ofir E.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2014)
The many-body Schrödinger dynamics of a one-dimensional bosonic Josephson junction is investigated for up to 10 000 bosons and long times. The initial states are fully condensed and the interaction strength is weak. We report on a universal fragmentation dynamics on the many-body level: systems consisting of different numbers of particles fragment to the same value at constant mean-field interaction strength. The phenomenon manifests itself in observables such as the correlation functions of the system. We explain this universal fragmentation dynamics analytically based on the Bose-Hubbard model. We thereby show that the extent to which many-body effects become important at later times depends crucially on the initial state. Even for arbitrarily large particle numbers and arbitrarily weak interaction strength the dynamics is many-body in nature and the fragmentation universal. There is no weakly interacting limit where the Gross-Pitaevskii mean field is valid for long times.